2019
DOI: 10.1111/pace.13828
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, depression, and anxiety in patients with a subcutaneous versus transvenous defibrillator system

Abstract: Background Use of the subcutaneous implantable defibrillator (S‐ICD) has increased because the device received US Food and Drug Administration approval in 2012, but we still know little about whether the quality of life (QoL) of patients with an S‐ICD versus a transvenous ICD (TV‐ICD) is comparable. We compared S‐ICD patients with TV‐ICD patients on QoL, depression, and anxiety up to 12 months’ follow‐up. Methods A matched cohort of S‐ICD (N = 167) and TV‐ICD patients (N = 167) completed measures on QoL, depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
5
11
0
Order By: Relevance
“…16,25 Data have been previously published on the quality of life of S-ICD patients. [26][27][28] Specifically, similar quality of life was found in S-ICD and transvenous ICD patients up to 6-and 12-months follow-up. 27,28 Moreover, while no differences were found between groups on psychological disorders and mental quality of life, physical quality of life seemed more impaired in transvenous ICD patients.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…16,25 Data have been previously published on the quality of life of S-ICD patients. [26][27][28] Specifically, similar quality of life was found in S-ICD and transvenous ICD patients up to 6-and 12-months follow-up. 27,28 Moreover, while no differences were found between groups on psychological disorders and mental quality of life, physical quality of life seemed more impaired in transvenous ICD patients.…”
Section: Discussionsupporting
confidence: 63%
“…[26][27][28] Specifically, similar quality of life was found in S-ICD and transvenous ICD patients up to 6-and 12-months follow-up. 27,28 Moreover, while no differences were found between groups on psychological disorders and mental quality of life, physical quality of life seemed more impaired in transvenous ICD patients. 26 However, currently no study has evaluated patient acceptance of S-ICD as a patient-centered outcome.…”
Section: Discussionsupporting
confidence: 63%
“…Previous observational research comparing S-ICD to TV-ICDs have yielded mostly comparable findings on generic QOL and general psychological functioning. 10,11 Both groups reported improvements by the 3-month mark and had sustained those improvements at 12-month follow up. Additionally, lower rates of anxiety and a greater reduction of depressive symptoms in the S-ICD group were noted.…”
Section: What Is Patient Acceptance and Why Does It Matter?mentioning
confidence: 93%
“…Additionally, lower rates of anxiety and a greater reduction of depressive symptoms in the S-ICD group were noted. 11 The use of device-specific QOL metrics (i.e., ICD QoL questionnaire) demonstrated that S-ICD patients had more severe perioperative pain, but were comparable on other aspects. 12 Vincentino et al (2022) 1 adds to this literature by further demonstrating that S-ICD patients accept their ICD as well as, if not better than, the TV-ICD patients.…”
Section: What Is Patient Acceptance and Why Does It Matter?mentioning
confidence: 99%
“…1 Implantable cardioverter defibrillator (ICD) is among such progresses in therapeutic technologies. 2 Evidence has indicated that ICD is superior to antidysrhythmic medications in reducing deaths resulting from cardiac dysrhythmias, as well as the risk of sudden cardiac death. 3 Moreover, ICD implantation has undergone considerable progresses in the recent years.…”
Section: Introductionmentioning
confidence: 99%